STORY CIRCLE TECHNIQUE TO HELP NON-ENGLISH MAJOR STUDENTS IN WRITING NARRATIVE TEXT - Abdul Aziz Rifaat (Institut Agama Islam Negeri Palopo, 2019)
The objective of this study was to find out the significant difference of the students in writing achievement before and after using Story Circle technique. The second objective was to find out the improvement of the students in writing achievement before and after Story Circle technique. The pre-experimental method through one group pre test-post test design was used in this study. The population and sample of the study was all 3rd semester students of S1 Nursing Science program at STIK Siti Khadijah Palembang in academic year 2018/2019. The total number of the population and sample was 35 students. The sample was taken by using total sampling technique. The tests were administrated twice as pre-test and post-test. After the pre-test was administered, the treatment was implemented. The post test was given after the treatment. The results of the tests were analyzed by using t-test through SPSS (Statistical Package for Social Science) program. The result of the study showed that there was a significant difference of the students in writing achievement before and after implementing Story Circle technique. It can be concluded that Story Circle technique could improve 3rd semester students’ writing achievement at of S1 Nursing Science program at STIK Siti Khadijah Palembang in academic year 2018/2019.